Response of FBG-bonded plastic plate at different locations of applied stress - Mohammed Salih, Younis (Penerbit UTM Press, 2016)
Fiber Bragg Grating sensing (FBG) has been intensively studied in the application of smart structures because of its immense advantages offered over those of the conventional sensors. In these researches unique characteristics of FBG, like its high sensitive resonance frequency spectrum and its resonant behavior were reported when FBG was coated by a ring-shaped material and used as an underwater acoustic sensor. In this study, the response of a FBG-bonded plastic plate at different locations of applied stress is demonstrated. The sensing element utilized for this purpose is a 10 mm FBG sensor bonded onto the surface of a plastic plate. Results of reflection spectrum showed that the output power increased randomly when the location of applied stress approached the location of FBG. This was assured from the increment of the area of reflection spectrum. The random increase in the output voltage was attributed to the insufficient stiffness of the plastic ruler, suggesting the implement of graphene plate instead of plastic ruler and increasing the grating length of FBG. The results showed an increase in the output power as detected by the photodiode. Consequently, a clear correlation between the optical and electrical outputs was observed.